Facilitating skills transfer: a collaborative writing centre intervention for undergraduate Law students - Drennan, Laura; Keyser, Gini (Journal for Language Teaching, 2022)
Despite the ability to write being central to success in the legal profession, there is general consensus concerning the poor writing skills of law graduates. In an attempt to address these concerns, this paper reports on the joint effort of subject experts and writing centre practitioners to address law students’ legal writing skills early on in their law degree. The objective of the study was to evaluate the potential impact of a blended, subject-specific writing intervention designed to address first-year Law students’ academic essay writing skills in terms of structure, organisation and argumentation. A multistage evaluation design was adopted to measure the potential impact of the intervention by collecting qualitative and quantitative data at various stages to triangulate the findings of the study. The results showed a statistically significant improvement in the submissions of students who engaged fully in the various stages of the writing intervention. This study contributes to research that shows that by embedding writing development initiatives in disciplines which form part of disciplinary course assessment, higher education institutions might begin to make headway in meeting their obligation to ensure that students possess the key graduate attributes that are required to make a contribution to the workplace.